Information needs and information seeking behaviour among users of UiTM Sarawak Library / Imilia Ibrahim, Sabariah Abd Samad and Favilla Zaini - Ibrahim, Imilia; Abd Samad, Sabariah; Zaini, Favilla (UITM Sarawak,Kampus Samarahan, 2010)
In order to provide the best information services to the users, libraries work very hard to provide the best information that they could afford. Therefore millions of Ringgit was spent every year for library services and products in Malaysia. Yet there are still people who are much distanced from the library. These people think that there is nothing available for them in the library or the libraries are not able to fulfill their information needs. The assumption might be true. This report is discussing on users of UiTM Sarawak Library information needs, their information seeking behavior and their attitude toward the UiTM Sarawak Library. A survey has been conducted where 330 users have answered the questionnaires and all the questionnaires have been analyzed. From 330 users, 288 were students while the rest were staff in various departments in the university. The survey have shown that most users go to the library to get general information. The prefer using the Internet where the Internet Search Engine has become their major source of information as well as their main research tools. They also prefer using the library only when they could not find anything on the net or when they want to borrow books. In general, most of the respondents rate the library services as satisfactory which leads to the reason why they do not go to the library often. From this research the library should improve in their online services and have more promotion of what they have in the library that would benefit the users